2022
DOI: 10.1108/bfj-04-2021-0441
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fixed and growth mindsets on buying sustainable foods

Abstract: PurposeFew marketing studies have studied consumer mindsets about sustainable products in developing countries. This paper examines the influence of fixed and growth mindsets on buying sustainable foods in Iran.Design/methodology/approachTo reach this goal, the authors designed a conceptual model and specified hypotheses. A non-probability survey of 622 people was conducted through a multistage cluster random sampling from two provinces in north Iran: Gilan and Mazandaran. Data were collected through a face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…In the green clothing context, fashion consciousness, environmentalism, social status and innovativeness are proved to be significant symbolic meanings that consumers want to express to others. The findings of the study are in line with the literature which investigates the impact of mindsets on environmental consumer behavior (Duchi et al , 2020; Rahnama and Leszczyc, 2022; Soliman and Wilson, 2017). The results of moderated mediation analyses prove that consumer mindset is the boundary condition for green clothing's symbolic meanings' indirect impact except for environmentalism symbol on purchase intention.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the green clothing context, fashion consciousness, environmentalism, social status and innovativeness are proved to be significant symbolic meanings that consumers want to express to others. The findings of the study are in line with the literature which investigates the impact of mindsets on environmental consumer behavior (Duchi et al , 2020; Rahnama and Leszczyc, 2022; Soliman and Wilson, 2017). The results of moderated mediation analyses prove that consumer mindset is the boundary condition for green clothing's symbolic meanings' indirect impact except for environmentalism symbol on purchase intention.…”
Section: Discussionsupporting
confidence: 86%
“…In the environmental consumer behavior context, two studies found that consumer mindset about the world's changeability (whether the world is stable vs changeable) might affect their beliefs about the effectiveness of environmental behaviors and intentions to engage in various environmental behaviors such as buying environmentally friendly products (Soliman and Wilson, 2017;Duchi et al, 2020). Besides, only one study investigated the relationship between mindsets about personality and buying sustainable foods (Rahnama and Leszczyc, 2022). The moderating role of mindset in the relationship between symbolic meanings of green products and consumers' attitudes toward green products is an under-researched area.…”
Section: The Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations